TREN PERDAGANGAN INTERNASIONAL DAN PENGARUHNYA TERHADAP NERACA PERDAGANGAN INDONESIA - Febi Safitri; Juliana Putri (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
International trade is an economic interaction between countries that enables the exchange of goods and services to meet domestic market needs and accelerate economic growth. Indonesia, as a country with an open economy, has a high dependency on export and import activities. This article aims to analyze the impact of current international trade trends, such as digitalization, protectionist policies, and the shift toward a green economy, on Indonesia's trade balance. This study employs a descriptive qualitative method using secondary data to evaluate these changes and their effects on export-import patterns. The findings indicate that these global trends pose challenges for Indonesia, particularly concerning its dependence on commodities and imported capital goods. The article also proposes strategies to enhance Indonesia's competitiveness through export product diversification and domestic industrial development, to maintain trade balance stability and strengthen Indonesia's position in the global market.